Toxic Communication on TikTok: Sigma Masculinities and Gendered Disinformation - Samuel Tanner; François Gillardin (Social Media + Society)
A growing body of research highlights digital platforms like TikTok’s pivotal role in shaping meaning for their users, particularly regarding gender perceptions. With TikTok increasingly serving as a search engine for teens, understanding how opinions are formed necessitates examining online content and interactions. Our article focuses on the construction of masculinity and gender dynamics with sigma videos on TikTok, emphasizing the digital practices that foster toxic communication. We define toxic communication as the deliberate framing and intensification of gender relations through the lens of male control and domination, alongside the denigration, devaluation, or defamation of feminine and non-binary identities associated with hegemonic masculinity. Adopting a socio-technical approach, we utilize a digital qualitative method of immersive observation to collect and analyze videos, posts, hashtags, and gender-related content. Our findings reveal that sigma toxic communication manifests in a spectrum ranging from subtle humor to explicit violence. This diversity of content functions as a “ready-to-think” framework, potentially appealing to a wide range of men across varying tastes, ages, and attitudes toward gender while perpetuating narratives that reflect and reinforce entrenched patterns of male dominance.